Manufacturing of reinforcing bars from COVID-19 syringes plastic waste and comparing them with different reinforcing bars - Nhabih, Hussein Talab; Baiee, Ameer; Al-Badkubi, Mohammad R.K.M.; Salman, Marwa Marza (Edelweiss Applied Science and Technology, 2025)
COVID-19 syringes plastic waste is difficult to recycle, so this study focuses on the use of this waste in manufacturing reinforcing bars as an alternative to steel reinforcing bars or carbon fiber reinforced polymer bars. After sterilizing COVID-19 syringes, these syringes are immersed in liquid nitrogen and then hammered to turn into random fibers. After spinning these fibers to the appropriate diameter, they are coated with a layer of epoxy to become reinforcing bars. To test the efficiency of these bars, six samples of concrete beams were cast. The first beam sample was reinforced with manufactured plastic bars made from COVID-19 syringes. The second and third beam samples were reinforced with deformed and plain steel reinforcing bars, respectively. The fourth beam sample was reinforced with carbon fiber reinforced polymer bars. Meanwhile, the fifth and sixth beam samples were reinforced with glass fiber reinforced polymer bars and basalt fiber reinforced polymer bars, respectively. The experimental results showed a 29.5%, 18.2%, and 6.8% increase in the ultimate load of the beam sample reinforced with the manufactured plastic bars compared to the beam sample reinforced with plain steel reinforcing bars, the beam sample reinforced with basalt fiber reinforced polymer bars, and the beam sample reinforced with glass fiber reinforced polymer bars, respectively.